Activation of delta-opioid receptor contributes to the antinociceptive effect of oxycodone in mice. (September 2016) - Yang, Pao-Pao; Yeh, Geng-Chang; Yeh, Teng-Kuang; Xi, Jinghua; Loh, Horace H.; Law, Ping-Yee; Tao, Pao-Luh
Graphical abstract: Abstract: Oxycodone has been used clinically for over 90 years. While it is known that it exhibits low affinity for the multiple opioid receptors, whether its pharmacological activities are due to oxycodone activation of the opioid receptor type or due to its active metabolite (oxymorphone) that exhibits high affinity for the mu-opioid receptors remains unresolved. Ross and Smith (1997) reported the antinociceptive effects of oxycodone (171 nmol, i.c.v.) are induced by putative kappa-opioid receptors in SD rat while others have reported oxycodone activities are due to activation of mu- and/or delta-opioid receptors. In this study, using male mu-opioid receptor knock-out (MOR-KO) mice, we examined whether delta-opioid receptor was involved in oxycodone antinociception. Systemic subcutaneous (s.c.) administration of oxycodone (above 40 mg/kg) could induce a small but significant antinociceptive effect in MOR-KO mice by the tail flick test. Delta-opioid receptor antagonist (naltrindole, 10 mg/kg or 20 mg/kg, i.p.) could block this effect. When oxycodone was injected directly into the brain of MOR-KO mice by intracerebroventricular (i.c.v.) route, oxycodone at doses of 50 nmol or higher could induce similar level of antinociceptive responses to those observed in wild type mice at the same doses by i.c.v. Delta-opioid receptor antagonists (naltrindole at 10 nmol or ICI 154, 129 at 20 μg) completely blocked the supraspinal antinociceptive effect of oxycodone in MOR-KO mice. Such oxycodone antinociceptive responses were probably not due to its active metabolites oxymorphone because (a) the relative low level of oxymorphone was found in the brain after systemically or centrally oxycodone injection using LC/MS/MS analysis; (b) oxymorphone at a dose that mimics the level detected in the mice brain did not show any significant antinocieption effect; (c) oxycodone exhibits equal potency as oxymorphone albeit being a partial agonist in regulating [Ca 2+ ]I transients in a clonal cell line expressing high level of mu-opioid receptor. These data suggest that oxycodone by itself can activate both the mu- and delta-opioid receptors and that delta-opioid receptors may contribute to the central antinociceptive effect of oxycodone in mice.